2021
DOI: 10.1186/s10194-021-01294-8
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the relationships between the burden of multiple sensory hypersensitivity symptoms and headache-related disability in patents with migraine

Abstract: Objective Sensory hypersensitivities such as photophobia, phonophobia, and osmophobia are common in patients with migraine. We investigated the burden of these multiple sensory hypersensitivities in migraine. Methods In this cross-sectional study, 187 consecutive patients with migraine (26 men/161 women; age, 45.9 ± 13.2 years) were included. Sensory hypersensitivity symptoms such as photo−/phono−/osmophobia and accompanying symptoms were determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…The prevalence of CS found in our study is in line with previous findings about chronic migraine or low back pain. 44 , 46 , 51 However, it is much higher than that in a Japanese study on chronic musculoskeletal pain (less than 30%). 31 The discrepancies could be explained by the different clinical characteristics of the sample population in the present study.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…The prevalence of CS found in our study is in line with previous findings about chronic migraine or low back pain. 44 , 46 , 51 However, it is much higher than that in a Japanese study on chronic musculoskeletal pain (less than 30%). 31 The discrepancies could be explained by the different clinical characteristics of the sample population in the present study.…”
Section: Discussionmentioning
confidence: 68%
“…The presence of CS has previously been evidenced in persistent pain disorders including chronic headache, musculoskeletal pain, as well as neuropathic pain. [44][45][46][47][48][49] CS can be measured by quantitative methods for heat and cold pain thresholds as well as pressure pain thresholds. 12,27,50 Given the time-and labor-consuming nature of QST measures, a CSI scale has been developed to screen CS in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a cross-sectional study, photophobia, phonophobia and osmophobia were observed in 75.4%, 76.5% and 55.1% of patients with migraine, respectively; these hypersensitivities exhibited substantial overlap, as the proportions of patients with 2 and 3 coexisting sensory hypersensitivities were 33.2% and 41.7%. 57 In the same study, the migraine Disability Assessment score was found to be higher in patients with 3 sensory hypersensitivities than in those with 0–2 sensory hypersensitivities. These results, which illustrate the burden of multiple hypersensitivity symptoms, may support the contribution of CS to migraine.…”
Section: Methodsmentioning
confidence: 82%
“…Another study however, did not find an association between disease duration and interictal olfactory hypersensitivity [8]. Data on subjective sensory hypersensitivity in 187 patients with migraine showed not only a common overlap of subjective sensory hypersensitivities to light, noise and smell but also a clear relation between sensory hypersensitivities and migraine disability [22]. Pre/ictal osmophobia has so far not been investigated in this context.…”
Section: Discussionmentioning
confidence: 95%